2022
DOI: 10.3390/cancers14102566
|View full text |Cite
|
Sign up to set email alerts
|

Use of Thiazide Diuretics and Risk of All Types of Skin Cancers: An Updated Systematic Review and Meta-Analysis

Abstract: Background: The use of thiazide diuretics is associated with skin cancer risk; however, whether this applies to all skin cancer types is unclear. Methods: In this meta-analysis, we searched multiple electronic databases and gray literature up to 10 April 2022, with no language restrictions, to identify relevant randomized controlled trials (RCTs) and non-randomized studies (cohort, case-control) that investigated the association between thiazide diuretics and skin cancer. The primary outcomes of interest were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 63 publications
0
24
0
10
Order By: Relevance
“…using the Cochrane risk-of-bias tool for randomized trials and the Newcastle-Ottawa Scale (NOS; score range: 0-9, with the higher scores indicating the higher quality of the study) for nonrandomized studies . The overall risk of bias was then categorized as low, high, or of some concern for randomized trials and the highest quality (NOS score ≥8 points) for nonrandomized studies . Any discrepancies in each review step were resolved through consensus discussion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…using the Cochrane risk-of-bias tool for randomized trials and the Newcastle-Ottawa Scale (NOS; score range: 0-9, with the higher scores indicating the higher quality of the study) for nonrandomized studies . The overall risk of bias was then categorized as low, high, or of some concern for randomized trials and the highest quality (NOS score ≥8 points) for nonrandomized studies . Any discrepancies in each review step were resolved through consensus discussion.…”
Section: Methodsmentioning
confidence: 99%
“…16 The overall risk of bias was then categorized as low, high, or of some concern for randomized trials and the highest quality (NOS score Ն8 points) for nonrandomized studies. 17,18 Any discrepancies in each review step were resolved through consensus discussion.…”
Section: Outcomes Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Whether HCTZ affects the skin in the same way remains unclear, because various studies have produced conflicting results. [6][7][8][9][10][11][12][13][14][15][16][17] HCTZ is currently being assessed for potentially co-carcinogenic effects in ultraviolet radiation (UVR)-induced skin cancer. [6][7][8][9][10][11][12][13][14][15][16] Previously, a significant dose-response relationship between HCTZ use and an elevated risk of SCC has been shown.…”
mentioning
confidence: 99%
“…6,[9][10][11][12][13] A meta-analysis found an association between using thiazide diuretics and an increased risk of all types of skin cancer, including MM. 17 Other studies have shown that HCTZ has little or no effect on the risk of developing BCC. 6,12 Jensen et al suggested that sun-protective measures alone may be insufficient to counteract the carcinogenic potential of HCTZ.…”
mentioning
confidence: 99%